6(x+5)=3(2x+4)+18

Simple and best practice solution for 6(x+5)=3(2x+4)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+5)=3(2x+4)+18 equation:


Simplifying
6(x + 5) = 3(2x + 4) + 18

Reorder the terms:
6(5 + x) = 3(2x + 4) + 18
(5 * 6 + x * 6) = 3(2x + 4) + 18
(30 + 6x) = 3(2x + 4) + 18

Reorder the terms:
30 + 6x = 3(4 + 2x) + 18
30 + 6x = (4 * 3 + 2x * 3) + 18
30 + 6x = (12 + 6x) + 18

Reorder the terms:
30 + 6x = 12 + 18 + 6x

Combine like terms: 12 + 18 = 30
30 + 6x = 30 + 6x

Add '-30' to each side of the equation.
30 + -30 + 6x = 30 + -30 + 6x

Combine like terms: 30 + -30 = 0
0 + 6x = 30 + -30 + 6x
6x = 30 + -30 + 6x

Combine like terms: 30 + -30 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| .8(x+40)+.2x=57 | | 24x+5x+67=24 | | 5d^2+5d-6=0 | | 12(3x+3)-7(2x-3)=12x-13 | | a=1b | | X=32+-3x | | .70x+.05(2-x)=.10(-64) | | (p+36)+p+(4p-37)=677 | | 3x=x+36 | | 3x=x+32 | | (5-c)(5+c)=0 | | .30(12)+.05x=.10(6+x) | | 3(6-3m)+5(2m+7)=0 | | 5c^2+5c+15=0 | | 25-c^2=0 | | (2/3)x=5(1/3) | | 9x=810 | | 2d-14=-24 | | 10x^2+5x-1=0 | | 3x=32 | | 10x^2+5y-1=0 | | -10=-3m+5 | | (3/4)8=x | | 3x-8=6x-26 | | x+6x=23 | | 3x-x=x+20 | | c/4=1/2 | | 10x-y*x-x^2-.5x^3=0 | | 2(3y-5)=-15 | | -4x+8=-25-7x | | x^2-7=74 | | x^3+2x^2-35x=O |

Equations solver categories